A ética enquanto práxis na educação da infância: um ensino em questão - Pereira, Nilda da Silva (2006)
ABSTRACT The main objective of this research was investigating the ethic as a curricular content and praxis of teaching in the infantile education (kindergarden). The investigation made possible to point out and evaluate the difficulties, limitations and successes in the ethic teaching practice in the scholar place of small children. The idea of researching ethic in the infantile education came out due to some schools in Mato Grosso do Sul state develop with their children educational projects and systemic classes related to citizen and values reflection. Classes about violence, environment care and each other care, traffic, hungriness and racial and or gender discrimination are common in these teaching establishments. These attempts show certain worries with problems managed daily. The fieldwork took place in an Infantile Education Center (CEI) in Campo Grande, Mato Grosso do Sul. The investigation had a qualitative approach; it is a case study with direct and participative observation. We centered the investigation answering to some unrest: Why is ethic taught at CEI? What is teaching ethic to a group of teachers? How is it structured ethic teaching at CEI? How is the ethic teaching in the practice? What are the problems faced? How do the teachers deal with these difficulties? After knowing why and how the CEI staff teaches ethic, we analyzed critically the work. We enclose our work making some considerations that are going to be passed to the CEI group in study meetings